Examining the relationship between operational risk, credit risk and liquidity risk with performance of Malaysia Banks - Saeed, Maytham Hussein (2015)
This study examines the impact of risk management on bank performance in Malaysia. The data of this study are retrieved from DataStream and annual reports of all conventional banks in the country. The sample of the study comprises of 27 conventional commercial banks in Malaysia and the period of study is confined to 2005-2013; making up to 208 observations. The dependent variable of this study is bank performance and is proxy by ROA and ROE, while risk management is the independent variable and is proxy by operational risk, credit risk, and liquidity risk. A regression analysis with GLS estimation is run to test the hypotheses of the study and the results show that operational risk, credit risk and liquidity risk have significant influence on ROE. However, the regression results show that only operational risk and credit risk are significant to ROA while liquidity risk is found to have insignificant relationship with ROA. Hence, the hypotheses of the significant relationship of operational risk and credit risk with bank performance are supported while the hypothesis of significant relationship of liquidity risk and bank performance is not supported.